On-Line Photoinduced Fluorescence for Carbamazepine Determination after Multivariate Optimization - Henestrosa, Cecilia Mariel (2019)
This work presents a simple and sensitive flow injection fluorimetric methodfor the determination of carbamazepine (CBZ) in pharmaceutical samples. Itis based on the fluorescence signal measurement of the product generated byphotoinduced (λex = 251 nm; λem = 434 nm) using a flow injection manifoldcontaining an on-line homemade photoreactor. In order to optimize the experimental setup, the variable conditions were studied using a multivariateoptimization method, thus finding the set of optimum parameters accordingto the evaluated responses (sensitivity and sampling frequency) and minimizing the number of experiments performed. Under optimal experimentalconditions, linear relationship with good correlation coefficient (0.9956) wasfound between the fluorescence intensity and CBZ concentration in the rangeof 0.13 - 40 µg∙mL−1. The limit of detection was 0.04 µg∙mL−1. The precision ofthe method was satisfactory; the values of relative standard deviations werebetter than 4.36%. The proposed method was validated and successfully applied to the determination of CBZ in pharmaceuticals with good accuracy;being the recovery values from 89.45% - 112.20%.